Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Financial Technology Terhadap Perilaku Keuangan Mahasiswa - Putri, Eka Cahyani; Susanti, Susanti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi (e-Journal), 2024)
This research aims to analyze the influence of financial literacy, financial inclusion, and financial technology on student financial behavior. This type of research is quantitative research. The sampling technique used purposive sampling with the Slovin formula to obtain a total sample of 102 active student respondents from the Accounting Education Study Program at Surabaya State University. The data source used is primary data. The data collection method uses a questionnaire in the form of tests and statements. The data processing technique uses multiple linear regression methods which are analyzed using SPSS version 29 software. The research results simultaneously show that financial literacy, financial inclusion and financial technology have a significant influence on student financial behavior. Partially, it shows that financial literacy has no significant effect on financial behavior, while financial inclusion and financial technology have a significant effect on financial behavior.